1987
DOI: 10.1103/physrevc.36.115
|View full text |Cite
|
Sign up to set email alerts
|

Fission and quasifission in U-induced reactions

Abstract: Triple-differential cross sections have been measured as a function of product mass, total kinetic energy, and center-of-mass scattering angle in reactions induced by "'U on ' 0, Mg, "Al, "S, "Cl, Ca, Ca, and ""Zn targets at several bombarding energies between 4.6 and 7.5 MeV /nucleon. The analysis focuses on binary processes in which the product masses are substantially different from the target-projectile masses. These include the complete fusion followed by fission as well as quasifission processes in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
314
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 331 publications
(336 citation statements)
references
References 50 publications
21
314
1
Order By: Relevance
“…The time scales of certain quasi-fission reactions have been determined from the rotation angle of the system before breakup [2,12]. This method can provide an almost modelindependent estimate of time scales.…”
Section: Mass-angle Distributionsmentioning
confidence: 99%
“…The time scales of certain quasi-fission reactions have been determined from the rotation angle of the system before breakup [2,12]. This method can provide an almost modelindependent estimate of time scales.…”
Section: Mass-angle Distributionsmentioning
confidence: 99%
“…Quasifission mass-angle distributions (MAD) first measured at GSI in the 1980s [2,5] showed that quasifission timescales could often be shorter than the rotation time of ∼10 −20 s. However, subsequently only a few measurements [6,7] were made until recent years, when an extensive series of experiments (using the Australian National University Heavy Ion Accelerator Facility and CUBE spectrometer) were carried out [3,[8][9][10][11][12][13][14][15][16]. The kinematic coincidence technique used in the measurements [2,3,17] provides direct information on the mass-ratio of the fragments at scission; thus, the data are represented in terms of mass ratio M R , rather than pre-or According to the characteristics of the MAD (minimum mass yield at symmetry, mass-angle correlation with peak yield at symmetry, and no significant mass-angle correlation), they are assigned as type MAD1, MAD2 and MAD3 respectively [3].…”
Section: Introductionmentioning
confidence: 99%
“…CN formation, in contrast, is characterized by equilibration of all degrees of freedom, and hence completes loss of identity of the entrance channel. Intermediate between DIC and CN fission, QF has full energy dissipation but incomplete drift toward the energetically favoured mass-symmetric configuration [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Intensive studies of the mechanisms of complete fusion in fission experiments [4,6,7] and in experiments on ER production [9][10][11][12] in reactions leading to heavy and very heavy composite systems, make it evident that the growing QF effect leads to a rapid decrease in the fusion probability and consequently to the drop of production cross sections for the heaviest elements as their atomic number is increased. Such dependence is clearly seen in the case of 'cold' fusion reactions [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation